From Fixed to Fluid: A Narrative Inquiry into How First-Generation University Lecturers Construct and Negotiate Their Growth Mindset in the Face of Digital Transformation - Priyo Sasmito; Nur Latifah; Evi Erianty Hasibuan; Desi Meliana Gultom; Poppy Honora; Edi Epron Sihombing; Erlina Sari (International Journal of Educational Research Excellence (IJERE), 2026)
Digital transformation in higher education demands not only technological proficiency but also fundamental shifts in how lecturers perceive their professional roles and identities. This study explores how first-generation university lecturers in North Sumatra construct and negotiate their growth mindset amidst the forces of digital transformation. Employing a narrative inquiry approach, this research delves into the subjective experiences of lecturers as they adapt to the demands of digital pedagogy and navigate their beliefs about teaching ability shifting from a fixed to a more fluid growth-oriented mindset. The study was conducted across several higher education institutions in North Sumatra, involving participants who are first-generation academics in their families. Data were collected through semi-structured in-depth interviews and reflective document analysis, then analyzed using narrative thematic analysis. The findings reveal that digital transformation triggers tensions between long-held beliefs about the lecturer's role as the sole authority of knowledge and emerging demands to serve as facilitators of collaborative learning. The negotiation of growth mindset occurs through three primary processes: (1) acknowledgment of digital competency limitations as an entry point for learning, (2) pedagogical experimentation driven by student needs, and (3) critical reflection on both failures and successes in adopting technology. The socio-cultural context of North Sumatra including uneven digital infrastructure access and prevailing values of collectivism significantly influences how lecturers build resilience and openness to change. This study concludes that growth mindset is not an inherent trait but rather a narrative construct that is continuously negotiated through experience and reflection. These findings offer implications for professional development programs for Indonesian lecturers, particularly in designing training initiatives that emphasize not only technical skills but also the cultivation of adaptive professional identities in the digital era.